Quality of Medical Care for Minor Surgery in Urban Units of the First Level of Care - Alexandra Patricia Abata Erazo; Zuly Rivel Nazate Chugá; Erika León León (Medisur)
Background: minor surgery includes a series of surgical procedures, with simple and brief techniques, performed on superficial tissues or easily accessible structures, under local anesthesia and with little risk of post-surgical complications. Objective: to describe the quality of medical care for minor surgery in the urban units of the first level of care in the city of Tulcán, Ecuador. Methods: a descriptive, cross-sectional study was carried out in the urban units of the first level of care in the city of Tulcán, aimed at medical and nursing staff, which together total 42 professionals. These professionals underwent a survey related to the infrastructure, supplies, knowledge and performance of health personnel in minor surgery procedures. Results: health units do not have infrastructure, equipment, necessary supplies and a protocol that allows these procedures to be carried out safely, so patients have to be referred to the second level of care. Conclusions: the systematization of the action protocols, the implementation and the standardization of the minor surgery procedures guarantee the safety, relevance and opportunity of the action of the health personnel in favor of the users in the first level of care.